PENINGKATAN PEMAHAMAN PEMBELAJARAN PAI MATERI SHALAT MELALUI MEDIA GAMBAR KELAS IV SD NEGERI 0713 PIR TRANS SOSA I A TAHUN 2016 - Siti Holijah Ritonga (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
The background in this study is the lack of the use of learning media  in  a  matter  of  prayer  so  that  the  learning  achievement is  less.  The  method  used  in  this  research  is  a  class  act. Collecting  data  in  this  study  with  observation  and  interview methods.   In   the   data   analysis,   the   authors   used   data reduction, data display, tentative conclusions and verification. Results   of   this   research   is   student   interest   to   learn   the prayers  in  public  primary  schools  Pir  Trans  Sosa  0713  I  A after using media images has increased. In the pre-cycle to the first  cycle  students'  interest  increased  by  92.6%.  After  using media images of student achievement Elementary School 0713 Trans Sosa Pir I A increased from the first cycle to the second cycle  as  much  as  98.3%.  Students  who  have  not  yet  reached pre-cycle  KKM  on  as  many  as  13  students  and  reaching  the KKM  many  as  18  students.  In  siklusI  students  who  have  not reached  the  KKM  as  6  students  and  has  reached  the  KKM many as 25 students. In the second cycle students who have not achieved as much as 3 KKM KKM students and achieve as much as 29 students.